Herbal creams used for atopic eczema in Birmingham, UK illegally contain potent corticosteroids. Issue 12 (11th December 2003) - Ramsay, H M; Goddard, W; Gill, S; Moss, C
Abstract : Aims: To determine whether "herbal creams" reported as being effective for the treatment of childhood atopic eczema contained corticosteroids. Methods: Patients attending the paediatric dermatology clinic at Birmingham Children's Hospital, April 2001 to March 2002, and who reported using "herbal creams" with good effect for atopic eczema were asked to submit the cream for analysis. Hydrocortisone, clobetasone butyrate, betamethasone valerate, and clobetasol propionate were analysed by HPLC. Results: Twenty four creams from 19 patients, median (interquartile range) age 3.82 (0.69–7.98) years were analysed. All five creams labelled Wau Wa and the two labelled Muijiza cream contained clobetasol propionate. Thirteen of 17 unnamed creams contained corticosteroids: clobetasol proprionate (n = 4), clobetasol proprionate + hydrocortisone (n = 1), betamethasone valerate (n = 2), clobetasone butyrate (n = 3), and hydrocortisone (n = 2); there was an unidentified peak in one. Further analysis suggested Wau Wa cream contained approximately 20% proprietary Dermovate Cream in a paraffin base. No parents were aware that the creams contained steroid. Conclusions: The majority of herbal creams analysed illegally contained potent or very potent topical steroids. There is an urgent need for tighter regulation of herbal creams and for increased public education about the potential dangers of alternative therapies.